2013
DOI: 10.1038/cddis.2013.186
|View full text |Cite
|
Sign up to set email alerts
|

B4GALT family mediates the multidrug resistance of human leukemia cells by regulating the hedgehog pathway and the expression of p-glycoprotein and multidrug resistance-associated protein 1

Abstract: β-1, 4-Galactosyltransferase gene (B4GALT) family consists of seven members, which encode corresponding enzymes known as type II membrane-bound glycoproteins. These enzymes catalyze the biosynthesis of different glycoconjugates and saccharide structures, and have been recognized to be involved in various diseases. In this study, we sought to determine the expressional profiles of B4GALT family in four pairs of parental and chemoresistant human leukemia cell lines and in bone marrow mononuclear cells (BMMC) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Furthermore, B4GALT1 has been strongly linked with multidrug resistance (8,16), tumor sensitivity to cisplatin (17,18) and promotion of cell death signaling pathways (19). Additionally, the gene undergoes promoter methylation in several cancer types and consequent silencing of the gene (13,20,21).…”
Section: Multifaceted Roles Of 5'-regulatory Region Of the Cancer Assmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, B4GALT1 has been strongly linked with multidrug resistance (8,16), tumor sensitivity to cisplatin (17,18) and promotion of cell death signaling pathways (19). Additionally, the gene undergoes promoter methylation in several cancer types and consequent silencing of the gene (13,20,21).…”
Section: Multifaceted Roles Of 5'-regulatory Region Of the Cancer Assmentioning
confidence: 99%
“…The two isoforms are type II membrane-bound glycoproteins and reside in Golgi apparatus and a portion of the longer protein functions on the cell surface as a recognition molecule by binding with appropriate glycoside substrates (5). Consequently, the B4GALT1 plays important roles in numerous physiological and pathological processes such as inflammation, sperm-egg interaction, embryogenesis, and morphogenesis, development of the central nervous system, cell migration, cancer progression and metastasis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…CSCs exhibit similar properties to those of normal stem cells, suggesting that these signaling pathways are important in maintaining CSCs in a variety of cancers, including lung (5,27). Previous studies reported that ABCB1 expression was affected by the above signaling pathways (28)(29)(30). However, the association between ABCB1 and these signaling pathways should be further confirmed in NSCLC patients.…”
Section: Discussionmentioning
confidence: 93%
“…Linked to adverse outcome in patients with non-metastatic clear cell renal cell carcinoma . Associated with multi-drug resistance in leukemia (Zhou et al 2013) Upregulated by TNFα in prostate cancer cells -role in motility and invasion (Radhakrishnan et al 2011) …”
Section: :3mentioning
confidence: 99%
“…B4GALT1 transfers a galactose residue to terminal N-acetylglucosamine and is involved in the late processing of N-glycans. Upregulated B4GALT1 can predict adverse outcome in patients with non-metastatic clear cell renal cell carcinoma and is associated with multi-drug resistance in leukaemia (Zhou et al 2013). In prostate cancer cells, B4GALT1 can be upregulated by TNFα and is thought to have a role in cell motility and invasion (Radhakrishnan et al 2011).…”
Section: N-glycan Biosynthesis (Ost Complex N-glycan Processing)mentioning
confidence: 99%